Tugas Dan Fungsi Kantor Wilayah Hukum Dan Ham Lampung Dalam Pembentukan Program Legislasi Daerah - Agus Iskandar PP. (Law Faculty of Universitas Bandar Lampung, 2015)
Law and Human Rights of Lampung Regional Office in carrying out its duties and functions provide guidance in the field of law and human rights, especially the formation of legislation in the area of the program is expected to help the formation of a maximum in the planning process so as to produce a regional regulation of local regulatory. The problem in this thesis is how the duties and functions of the Law and Human Rights of Lampung Regional Office in the establishment of Local Legislation. The method used in this study is through normative and empirical approaches. Secondary data was obtained through library,and the primary data obtained through field study. data analysis of qualitative analysis. Conclusion in this study is the duties and functions of the Department of Law and Human Rights of Lampung as an arm of Kemenkumham and play a role in the harmonization and synchronization in Prolegda formation.